2012
DOI: 10.1093/jb/mvs063
|View full text |Cite
|
Sign up to set email alerts
|

Moloney murine leukemia virus integrase and reverse transcriptase interact with PML proteins

Abstract: Pull-down assay and co-immunoprecipitation of cell extracts in which the integrase or reverse transcriptase of Moloney murine leukemia virus was transiently expressed showed that both enzymes interacted with PML proteins. In infected cells, interaction between the integrase and PML was also observed. Transient expression of PIASy and SUMO proteins facilitated SUMOylation of the integrase but had no apparent effects on the interaction with PML. A FLAG-tagged integrase co-localized with PML protein possibly in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The retroviral IN protein mediates the integration of provirus into the host genome [151,152]. The IN proteins of both HIV-1 and the MoMuLV can be SUMOylated [153,154]. It has been found that IN can be SUMOylated on three Lys residues (K46, K136 and K244) [154].…”
Section: Sumoylation and Retroviruses Infectionmentioning
confidence: 99%
“…The retroviral IN protein mediates the integration of provirus into the host genome [151,152]. The IN proteins of both HIV-1 and the MoMuLV can be SUMOylated [153,154]. It has been found that IN can be SUMOylated on three Lys residues (K46, K136 and K244) [154].…”
Section: Sumoylation and Retroviruses Infectionmentioning
confidence: 99%